Visceral leishmaniasis in immunosuppressed Caucasian patient. (8th May 2012) - TOQEER, Muhammad; Rahman, Nadeem; Whitehead, Mark W; Lockwood, Diana
Abstract : A 64-year-old man was admitted with fever, weight loss, fatigue and night sweats. He was known to have rheumatoid arthritis and had been taking methotrexate for 1 year. He had worked in Saudi Arabia until 1994 and had been living in Spain for 6 months every year. Clinical examination showed an enlarged spleen. Routine investigations showed pancytopaenia. Serial blood cultures were negative. CT scan confirmed splenomegaly and was otherwise unremarkable. Bone marrow biopsy revealed Leishmania amastigote consistent with a diagnosis of visceral leishmaniasis. After discussing with the hospital for tropical diseases (HTD), he was started on liposomal amphotericin B. Following two infusions of amphotericin B, he started improving as his fever, night sweats and weakness had settled. He was then discharged and followed up in HTD clinic 4 weeks later where he was found to be consistently improving.